Adaptation Strategies for Fish Farmers Facing Climate Change in Southwestern Nigeria - Grace Modupe Adebo; Tolu Anthony Ayelari (Advances in Aquaculture and Fisheries Management, 2024)
Production systems and livelihoods in South Western Nigeria are at risk of climate variability and change; the fisheries sectors are no exception. The study examined the vulnerability of fish farmers in Ondo and Ekiti States of Nigeria to Climate change. A total of 120 respondents were purposively selected, interviewed and used for data analysis. Result indicated that the fish farmers in Ondo and Ekiti States witnessed unprecedented change in weather conditions as reflected in unusual excessive downpour of rain thus affecting their productivity through flooding. Most of these fish producers were young, mainly males, literates, and experienced fish farmers but relied mainly on personal savings and money borrowed from friends and relatives for fish farming. They practiced the extensive system of fish culture, utilizing local feeds and depended mainly on streams, rivers and rainfall. Fish production is concentrated in wet season. Most farm sizes were below 1 ha, and utilized earthen pond. About 65% experienced flooding with about 61.6% loosing within 3501 to 5000 fishes at a time. All categories of fishes were flooded. Majority of the fish farms were not insured by any insurance company while the few that were insured experienced untimely and inadequate compensation, also very few received compensation from the Government. Climate change resulted in low productivity, low income, starvation, poor health as well as poor standard of living of the respondents.